Hug your haters : how to embrace complaints and keep your customers - Baer, Jay, 1969- (New York : Portfolio/Penguin, 2016)
"Haters are not your problem. Ignoring them is. Eighty percent of companies say they deliver outstanding customer service, but only 8 percent of their customers agree. This book will help you close that gap by reconfiguring your customer service to deliver knockout experiences. The near-universal adoption of smartphones and social media has fundamentally altered the science of complaints. Critics ("haters") can now express their displeasure faster and more publicly than ever. These trends have resulted in an overall increase in complaints and a belief by many businesses that they have to "pick their spots" when choosing to answer criticisms. Bestselling author Jay Baer shows why that approach is a major mistake. Based on an extensive proprietary study of how, where, and why we complain, Hug Your Haters proves that there are two types of complainers, each with very different motivations: ·Offstage haters. These people simply want solutions to their problems. They complain via legacy channels where the likelihood of a response is highest--phone, e-mail, and company websites. Offstage haters don't care if anyone else finds out, as long as they get answers. ·Onstage haters. These people are often disappointed by a substandard interaction via traditional channels, so they turn to indirect venues, such as social media, online review sites, and discussion boards. Onstage haters want more than solutions--they want an audience to share their righteous indignation. Hug Your Haters shows exactly how to deal with both groups, drawing on meticulously researched case studies from businesses of all types and sizes from around the world. It includes specific playbooks and formulas as well as a fold-out poster of "the Hatrix," which summarizes the best strategies for different situations. The book is also filled with poignant and hilarious examples of haters gone wild, and companies gone crazy, as well as inspirational stories of companies responding with speed, compassion, and humanity. Whether you work for a mom-and-pop store or a global brand, you will have haters--and you can't afford to ignore them. Baer's insights and tactics will teach you how to embrace complaints, put haters to work for you, and turn bad news into good outcomes"--
"Hug Your Haters How to Embrace Complaints and Keep Your Customers Jay Baer Based on proprietary research and more than 70 exclusive interviews, New York Times bestselling author Jay Baer offers a new playbook for handling unhappy customers. Hug Your Haters provides the recipe for a mobile, social, right-now world where complaints are faster and louder than ever. Technology has evaporated the barriers of complaint. With smart phones and always-on Internet access, consumers complain more often and across more channels, many of them public. This requires a completely new system for instantly finding, evaluating, and addressing these complaints. Jay Baer and Edison Research conducted a landmark study of more than 2,000 consumers and found that not all complainers ("haters") are created equal. In fact, there are two vastly different categories of haters: Offstage Haters and Onstage Haters. Baer also includes The Hatrix, a detailed examination of the differences between Offstage and Onstage haters. The book reveals: how, where and why people complain (by demographic and by channel) how and when consumers expect a response to their complaints the advocacy impact of answering (or ignoring) a hater differences in complaint type and expectations by industry"--
Includes bibliographical references and index.
Keywords: Customer relations; Consumer complaints; Marketing; BUSINESS & ECONOMICS / Customer Relations; BUSINESS & ECONOMICS / Marketing / General; BUSINESS & ECONOMICS / Consumer Behavior